Media Pembelajaran tentang Pola Makan Seimbang Bagi Anak-Anak Usia 4–6 Tahun Melalui Permainan - Hendriani, Maria (Institute of Research and Community Outreach - Petra Christian University, 2010)
Today, junk food has become the staple food favored by children. Therefore research is needed in the creation of media aids that provide information and explanation of a balanced diet for children, so children can understand about healthy and unhealthy food for their growth and bodies. This research used observational methods, interviews, and descriptive qualitative analyses. The study started from the media analysis of good learning, child psychology, intellectual games, and the importance of image. Appropriate learning media strategy for children is acquired from the results of the analysis. The delivery of messages is done using a 3-dimensional board game where there are several problems in the game which aims to remind and provide further explanation to children.